Влияние порошка железа на характеристики зажигания и горения смесевых твердых топлив - Коротких А. Г. Александр Геннадьевич; Архипов В. А. Владимир Афанасьевич; Глотов О. Г. Олег Григорьевич; Кискин А. Б. Александр Борисович; Зарко В. Е. Владимир Егорович (2015, 2015)
Заглавие с экрана